Cryptographic key Generation Using Fingerprint Biometrics - Ameer , Huda (University of Thi-Qar Journal of Science, 2015)
At the present time progress of communications technologies has resulted to post large amounts of digital data in the media shared among the people, this has necessitated the development of cryptographic techniques to be one of the building blocks for the security of the computer, so that became the encryption feature increasingly important to the  security of the computer. This paper proposed a method for generating a key using fingerprint features to ensure the  security of the system against hackers. This technical consists of two parts the first is the EPROM memory filled with information of fingerprint after processed by the enhancement, binarization and thinning operations and then 512 numeric values has been extracted. The second part is a set of linear shift registers where every movement for system  registers is an address in the memory where the dimensions of memory (8x64), the first three registers give the row address while the registers ordered by two to seven give the column address of EPROM array. The strength of the chain of random numbers which produced by making originating from two different worlds linked to the same user, is a goal makes this technique useful for several uses, such as using output as encryption keys, or use it as a digital series for personal definition for security systems.